Mass Spectrometry for the Structural Elucidation of Peptide-Based Therapeutics (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
In recent decades, the life sciences have undergone a paradigm shift in the strategies used to characterize genes, proteins, transcriptomes, and metabolites. This transformation has been propelled by the advent of high-throughput analytical platforms, which enable the simultaneous interrogation of vast numbers of biomolecules with unprecedented efficiency and resolution. Among these technologies, mass spectrometry has emerged as a cornerstone methodology, owing to its unrivaled sensitivity, selectivity, and quantitative power in ion detection. By facilitating the accurate reconstruction of the molecular and chemical architecture of complex biological systems, mass spectrometry has become indispensable to contemporary biological and biomedical research, driving advances in systems biology, drug discovery, and personalized medicine.MS enables high-throughput measurement of complex protein or peptide mixtures, sequencing and quantifying proteins or peptides, detecting post-translational modifications (PTMs) of proteins, and predicting their 3D folding and topology. Peptides and proteins are typically studied using mass spectrometry because traditional ionization techniques easily generate protonated species. Peptide drug conjugates (PDC) are a prodrug type in which drug molecules are conjugated  to peptides by covalent bonding via specific linkers.  The fragmentation of this PDC type depends on several parameters, such as instrument settings, solvent composition, and fragment ion intensities and types, which also depend on the structure. A novel conjugate of Anthracycline and peptide provides safe and effective cancer therapy. For its structure elucidation via MS, several detection techniques would be complementary.